Effect of cushion types on the seismic response of structure with disconnected pile raft foundation. (February 2023) - Yang, Yang; Cheng, Yi Pik; Gong, Weiming; Fan, Hong; Dai, Guoliang
Abstract: In recent years, the benefits of reducing the impacts of the earthquake on the seismic response of disconnected pile raft foundation (DPRF) have simulated increasing research on this type of foundation to provide references for foundation design. One effective way to study the seismic response of soil-structures is to investigate the scaled models in 1-g shaking table tests. In this paper, a series of scaled 1-g shaking table tests were carried out to study the seismic response of scaled nuclear power stations with DPRF under earthquake excitations founded in clay. Three different cushion types were adopted to study their different effects on the seismic response of the structure and the foundation. The fundamental structural frequency, horizontal displacement, and acceleration results showed that cushion A with well-graded gravel and cushion B with a mixture of two gravel sizes were better than cushion C with a single gravel size. Although the cushion type had an insignificant influence on the bending moments of the disconnected piles, the maximum bending moments in all cases were found to be proportional to the near-pile acceleration. Furthermore, design engineers should pay more attention to the rocking of a structure with DPRF under earthquake loads.